The Birth Story of Buddha from Nidānakathā and Lalitavistara: A Comparative Study of the Content - Sirisawad, Natchapol (Journal of Buddhist Studies Chulalongkorn University, 2021)
This research article is a comparative study of the birth episode of the Bodhisattva residing in the Tuṣita Heaven to the utterance of the Āsabhivācā in the biography of the Śākyamunī Buddha between the Nidānakathā in the Jātakaṭṭhakathā of the Theravādins, an introductory chapter of the Jātaka commentary which narrates the story of the Buddha in Pāli, and the Lalitavistara of the Sarvāstivādins, a Buddhist Sanskrit Buddha’s biography. The purposes of this research article are to (1) comparatively study the Buddha’s biography in the birth episode from the Nidānakathā and the Lalitavistara; and (2) examine significant concepts in the compilation of the Buddha’s birth narrative from both schools in order to understand similarities, differences, and specific features of the Buddha’s biography in each version. This research is of a descriptive nature; it investigates documents from both primary and secondary sources. The comparative study of both scriptures reveals that the Buddha’s birth episode of both schools narrates similar stories revolving around the same events but with different details, and stories that appear only in either the Nidānakathā or the Lalitavistara. Most of the coinciding stories of the two schools are the Buddha’s biography compiled on the basis of the rule of a Bodhisattva, which appears in the Pāli Mahāpadānasutta or the Sanskrit Mahāvadānasūtra, and the marvelous qualities of the Buddha in the Pāli Acchariyabbhutadhammasutta, which can be likened to the main plot of the Buddha’s birth episode, covering the descent of the Bodhisattva from the Tuṣita heaven, the time in his mother’s womb, and his birth. In addition, the events surrounding the birth story in the Buddha’s biography emphasize the “virtues” of the Bodhisattva as a person excelling in the dharma over all ordinary people, which serves to create faith in the Buddha.